The first end-on bonded superoxo complexes of Ga and In: the oxygen-rich compounds GaO4 and InO4 - Gaertner, Benjamin; Köhn, Andreas; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2006)
We report the first sighting and characterization of the oxygen-rich molecules GaO4 and InO4, being the products of a three-step process taking place in an Ar matrix. This process includes (i) reaction of Ga or In atoms (M) with one dioxygen molecule to give the cyclic superoxo complex MO2, (ii) photoisomerization into linear OMO by the action of UV light, and (iii) reaction of linear OMO with an additional O2 molcule. The molecules can be described as end-on bonded superoxo complexes OMO(O2). On the basis of the observed isotopic data the O-Ga-O angle can be estimated to be ca. 165°. In addition to the experimental studies, quantum chemical calculations were performed to achieve a more complete characterization of these interesting new and unusual molecules, representing the first ever found examples of end-on bonded superoxo complexes of Ga and In.
Gesehen am 14.03.2018; im Zusatztitel ist "4" tiefgestellt